Sviluppo turistico e governance territoriale nelle aree protette periurbane il parco regionale del Partenio - Corbisiero, Fabio; La Rocca, Rosa Anna; Zaccaria, Anna Maria; Zaccaria, Anna Maria (Smart City, Urban Planning for a Sustainable Future, 2023)
This book collects the contributions presented during the summer school Sc.OUT (University Observatory on Tourism) held in Partenio Regional Park from 28th June to 3rd July 2022. The focus concerns the relationship between tourism development and protected areas with the aim of identifying sustainable and compatible uses with the characteristics of natural territories. The Partenio's regional park has been considered as a first test for non-invasive hypotheses of land use adapt for tourism and leisure activities. The particularity of the Park's territory both as an area with high environmental value located in a peri-urban context and with high population densities represented a first challenge for achieving the objectives of Sc.OUT's project. Through a multi-interdisciplinary approach, authors highlighted how tourism development requires careful planning and monitoring to reach the equilibrium between development and safeguard of these territories.